2012
DOI: 10.1161/strokeaha.111.626853
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Intracerebral Hemorrhage in Patients With Cerebral Microbleeds Undergoing Endovascular Intervention

Abstract: Background and Purpose-Cerebral microbleeds (CMBs) on MRI gradient echo images are hemosiderin deposits, which may predict intracerebral hemorrhage (ICH). The risk of ICH in patients with CMBs could be exacerbated by the use of antithrombotics. The purpose of our study is to prospectively evaluate the risk of ICH in patients with ischemic stroke who receive dual antiplatelet therapy for endovascular intervention. Methods-We analyzed MRI of 133 patients admitted consecutively for intra-and extracranial stenting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…17 In patients with CMBs, the number of CMBs is usually positively skewed with a wide range (1-93 per person in ischemic stroke cohort), 18 meaning that the majority of people have only 1 or 2 CMBs and only a small portion of patients have ≥5 CMBs (17.4% in ischemic stroke patients with CMBs). 19 Overall, CMBs are not uncommonly found in subjects with ischemic stroke/TIA, who require antithrombotic therapy. At least about a quarter of these subjects harbor CMBs.…”
mentioning
confidence: 99%
“…17 In patients with CMBs, the number of CMBs is usually positively skewed with a wide range (1-93 per person in ischemic stroke cohort), 18 meaning that the majority of people have only 1 or 2 CMBs and only a small portion of patients have ≥5 CMBs (17.4% in ischemic stroke patients with CMBs). 19 Overall, CMBs are not uncommonly found in subjects with ischemic stroke/TIA, who require antithrombotic therapy. At least about a quarter of these subjects harbor CMBs.…”
mentioning
confidence: 99%
“…However, patients with multiple CMBs had an increased post-thrombolytic bleeding risk 11. The negative effect of a small number of CMBs on the intracranial bleeding risk is also supported by a study of intracranial and extracranial stenting for 133 patients with symptomatic large artery atherosclerosis 26. These results suggest that a small number of CMBs does not increase the risk of intracranial hemorrhage after IV thrombolysis, mechanical thrombectomy, and intracranial stenting.…”
Section: Discussionmentioning
confidence: 86%
“…One study showed that dual antiplatelet therapy was beneficial after endovascular intervention in patients with CMB. 7 Another study revealed that for ischemic stroke patients taking antiplatelet agents, CMB did not increase the risk of cerebral hemorrhage. 11 Even for patients with more than four CMBs, antiplatelet therapy still should be continued in the first year after ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%